Supporting modularization in textual DSL development - Irazábal, Jerónimo; Pons, Claudia Fabiana (2010)
A domain-specific language DSL provides a notation tailored towards an application domain. The closer the language is to their target domain, the more useful the language is for developers. But this increment in the level of specificity raises the issue of duplication of concepts among different languages, and leads to the definition of a family of languages. Despite the advance in tool support for defining the abstract and concrete syntaxes of DSLs, developing a family of DSLs still requires a significant amount of duplicated effort. In this work we present an infrastructure for implementing families of textual DSLs. We introduce a technique based on XText that reduces the effort required to create editors and interpreters by enabling the modularization of the common features and the smooth specification of variability between the DSLs.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
International Conference of the Chilean Computer Science Society (29ª : 2010 nov. 15-19 : Antofagasta), pp. 124-130
Keywords: LENGUAJES DE DOMINIO ESPECÍFICO - DSL